2020
DOI: 10.1097/md.0000000000021634
|View full text |Cite
|
Sign up to set email alerts
|

A novel compound heterozygous mutation in the arginase-1 gene identified in a Chinese patient with argininemia

Abstract: Introduction: Arginineemia, also known as arginase deficiency, is a rare autosomal recessive metabolic disease. The diagnosis sometimes may be delayed due to atypical clinical manifestations. Confirmation of arginineemia depends on genetic testing. Patient concerns: We reported a Chinese male child presenting with hyperargininemia and progressive spastic diplegia, who has a novel compound heterozygous mutation in the arginase-1 ( ARG1 ) gene (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…An update of the searches to capture studies published since the date of the last search (April 20, 2020) to July 06, 2021 identified 6 new relevant case studies reporting 13 individual cases with ARG1 mutations. 30 , 31 , 32 , 33 , 34 , 35 The results from these studies were consistent with the main findings presented in this review and further support the burden of ARG1‐D and the need for effective treatments.…”
Section: Resultssupporting
confidence: 89%
“…An update of the searches to capture studies published since the date of the last search (April 20, 2020) to July 06, 2021 identified 6 new relevant case studies reporting 13 individual cases with ARG1 mutations. 30 , 31 , 32 , 33 , 34 , 35 The results from these studies were consistent with the main findings presented in this review and further support the burden of ARG1‐D and the need for effective treatments.…”
Section: Resultssupporting
confidence: 89%
“…There is growing awareness in the literature surrounding the risk of missed or delayed diagnosis of ARG1‐D, and several reports include recommendations that IEMs, and ARG1‐D in particular, be considered in the differential diagnosis for patients with slowly progressing neurologic manifestations or neurologic regression, especially when progressive spasticity is present. 15 , 27 , 33 , 34 , 35 Specifically, the challenge of identifying ARG1‐D in patients with manifestations characteristic of HSP has been addressed. 25 Features suggesting ARG1‐D include pronounced worsening of spasticity and avoidance of high‐protein foods, but interestingly, the latter was not apparent in the patients described here.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Preliminary symptoms also include irritability, vomiting and feeding issues, and failure to thrive [ 1 ]. Hyperammonemia can occur but is usually less frequent and less severe when compared to other UCDs [ 4 ] .…”
Section: Introductionmentioning
confidence: 99%